A nature-inspired interface design strategy of carbon fiber composites by growing brick-and-mortar structure on carbon fiber. (10th November 2020) - Jin, Lin; Zhang, Mengjie; Shang, Lei; Liu, Liu; Li, Ming; Ao, Yuhui
Abstract: Poor interfacial interaction and damage-tolerance restrict practical application of carbon fiber (CF) composites. The brick-and-mortar structure meets the requirements of high strength and small crack growth behavior of composites. However, uniformly fabricating the three-dimension brick-and-mortar structure as an interface layer on CF surface remains a challenge. To fill up this technical gap, herein, 3D brick-and-mortar structures were uniformly constructed on carbon fiber surface via in-situ growth. Ni(OH)2 nanosheets which the morphology matched the geometry of fiber were used as the "brick", while multifunctional polydopamine (PDA) was employed as "mortar" that guarantees the powerful bonding interactions with "brick". The synergistic effects of composites were demonstrated through interlaminar shear strength (ILSS) and flexural tests, and the optimize ILSS and flexural performance were obtained from the composites with superior interface, which showed respectively 53.5% and 95.6% enhancement compared to the pristine CF/EP, presumably due to the brick-and-mortar structure arising from stress dissipation, plastic deformation and physical and chemical entanglements. This system could be applied on other three dimensional materials, overcoming the limitation of mimic nacre-like materials only achieved in the form of films. Graphical abstract: Image 1